2021
DOI: 10.1021/acs.langmuir.0c03408
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility of Multicomponent, Charged Model Biomembranes Tunes Permeation of Cationic Nanoparticles

Abstract: Cells respond to external stress by altering their membrane lipid composition to maintain fluidity, integrity and net charge. However, in interactions with charged nanoparticles (NPs), altering membrane charge could adversely affect its ability to transport ions across the cell membrane. Hence, it is important to understand possible pathways by which cells could alter zwitterionic lipid composition to respond to NPs without compromising membrane integrity and charge. Here, we report in situ synchrotron X-ray r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…Consequently, there arises a need for greater energy to trigger the unbinding transition through membrane bending. As mentioned earlier, the unbinding of CQDs from the O1G1 membrane was also independently observed in a separate study by us 44 involving SLBs as the membrane model, thus confirming that the unbinding phenomenon observed here is a robust result irrespective of the structure of the membrane model. The schematic in Fig.…”
Section: Effect Of Nanoparticle Concentration: Crowding and Electrost...supporting
confidence: 90%
See 2 more Smart Citations
“…Consequently, there arises a need for greater energy to trigger the unbinding transition through membrane bending. As mentioned earlier, the unbinding of CQDs from the O1G1 membrane was also independently observed in a separate study by us 44 involving SLBs as the membrane model, thus confirming that the unbinding phenomenon observed here is a robust result irrespective of the structure of the membrane model. The schematic in Fig.…”
Section: Effect Of Nanoparticle Concentration: Crowding and Electrost...supporting
confidence: 90%
“…The unbinding transition of NPs was also associated with a corresponding loss of lipids, suggesting a cooperative process underlying the transition. Our recent studies 44–49 also seem to suggest similar NP concentration-dependent mammalian model bilayer membrane disruption and lipid–NP complex formation on the membrane surface.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Preferential association of NPs with specific membrane domains is known to depend on the surface chemistry of NPs 49 and the mechanical properties of the membrane domains. 50 Previous atomistic simulations have shown that amphiphilic Janus NPs preferentially insert into Ld membrane domains that have less stringent packing constraints compared to Lo domains. 18 In contrast, our study reveals Janus NP-membrane interactions on a significantly larger length scale by examining the collective membrane compression effect of multiple Janus NPs on micron-sized vesicle membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The encapsulation technique makes it possible to create NCs with the same hydrophobic-polymeric shell and tune physical-chemical properties by controlling various functional group ratios on the surface. The following charged groups can provide a particular surface change and colloidal stability of QDs in aqueous media: carboxyl; [10][11][12][13][14][15][16][17][18][19] phosphate; [13,20] carboxybetaine/mixture of quaternary ammonia and carboxyl; [12,14] sulfobetaine; [12,17,21,22] primary, [15,23,24] secondary, [25] tertiary, [18] and quaternary ammonium. [14,19,26] The corresponding physicalchemical characteristic of QDs modified with the abovementioned surface groups are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%